Developing Positive School Climate for Inclusive Education - Wulan, Riwu; Sanjaya, Wira (Angstrom Centre of Education, 2022)
A positive school climate enables inclusive education to be implemented in order to achieve its goals. However, many school administrators face difficulties in building a positive school climate for inclusive education yet articles that discuss the school climate in the context of inclusive education in particular are still lacking. In this article, through a systematic search on the methodology of literature review, we categorize characteristics of positive school climate for inclusive education into sense of physical and social-emotional security, learning process that supports student self-development as a whole, supportive relationships and respect for individual differences, school environment that creates sense of belonging and encourages active participation of school members, leadership and professional relationship that cultivate positive attitude toward inclusive education. We also provide strategies on how to build positive school climate for inclusive education.